Diagnostic possibilities of the single-balloon enteroscopy - Ye. D. Fedorov; Ye. V. Ivanova; M. Ye. Timofeyev; P. L. Chernyakevich; O. N. Andreyeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. Main questions which arise both at the attending physician, who prescribes investigation of the small intestine, and at endoscopist doctor who plans to perform this invasive intervention are discussed. History of the issue, indications, contraindications and restrictions of this method, technical aspects of investigation, diagnostic and medical options of deep enteroscopy are briefly covered.Original positions. Being based on literature data and personal experience authors show, that balloon enteroscopy provide stable access to deep regions of the small intestine and helps to carry out high performance diagnostics of its diseases. The option of biopsy of mucosa and medical interventions is one of the most attractive features of this method.Conclusion. Authors believe, that wide application of deep enteroscopy in clinical practice will change existing concept on frequency, origin and nature of various pathological changes of small intestine.